ANALISIS KAUSALITAS ANTARA VOLATILITAS SAHAM DENGAN VARIABEL MAKROEKONOMI INDONESIA - Maria S Sitanggang; Paidi Hidayat (Departemen Ekonomi Pembangunan USU, 2013)
This study aims to know whether there is a significant interrelationship between the stock volatility (Jakarta Composite Index ) and the macroeconomic variables (Inflation and BI Rate) in Indonesia. The test is carried out using Stationarity Test, Cointegration Test, Granger Causality Test, and Vector Auto Regression (VAR) test for the period 2008.1 – 2012.12. From Cointegration test results that there is no long-term equilibrium relationship between Jakarta Composite index, BI Rate, and Inflation. While Granger Causality test result revealed that there is a direct relationship the inflation affect the Jakarta Composite Indexand there is reciprocal relationship between the BI Rate and the Jakarta Composite Index. Based on the result of impluse Response Function, it was found that the stock volatility (Jakarta Composite Index) has a negative effect on the macroeconomic variables (Inflationand BI Rate), similarly the macroeconomic variables (Inflation and BI Rate) has a negative effect on the Jakarta Composite Index. While the result of variance decomposition showed that the role of Inflation and BI rate is significant than Jakarta Composite Index.Keywords: Jakarta Composite Index, Inflation, BI Rate, Granger Causality, VAR.